Pengaruh Pemberian Aromaterapi Terhadap Konsentrasi Siswa Kelas V Sekolah Dasar dalam Mengerjakan Soal Ulangan Umum - Agustini, Ni Made Yanthi Ary; Sudhana, Hilda (Jurnal Psikologi Udayana, 2014)
Aromatherapy in Balinese life very closely. Aromatherapy has an influence on the function of the body such as making a fresh indoor air, creating a calm, can be used as antibiotics, antiseptics may be useful to take the fight against the virus, soaking emotion, can be a tool for relaxation, and also improves concentration. Concentration in the world of education is a very important one in doing general replications. This study aimed to verify whether there are effects of aromatherapy to the concentration of children in the fifth grade of primary school working on the general test questions. This research is a quantitative study with pre-experimental methods, sampling technique used is cluster random sampling. Subjects in this study were fifth grade elementary school students who are following the general replication at SD Negeri 5 Tonja by 82 students. Collecting data using a concentration questionnaire with Likert scale and data analysis by independent sample t-test. After conducting validity and reliability there are 25 items left from a total of 34 items on the reliability coefficient of 0.876. After doing               the independent sample t-test significance p values obtained for 0.823 (> 0.05). This means there is no effect of aromatherapy to the concentration of children in the fifth grade of primary school working on the general test questions.  Based  on  additional  data  to  see  the  concentration  of  each  day,  there  is  an increasing concentration in the experimental group students, but has not reached a significant point.   Keywords: Aromatherapy, Concentration, Students, General Test